The Kondo temperature of a two-dimensional electron gas with Rashba spin–orbit coupling. (5th August 2016) - Chen, Liang; Sun, Jinhua; Tang, Ho-Kin; Lin, Hai-Qing
Abstract: We use the Hirsch–Fye quantum Monte Carlo method to study the single magnetic impurity problem in a two-dimensional electron gas with Rashba spin–orbit coupling. We calculate the spin susceptibility for various values of spin–orbit coupling, Hubbard interaction, and chemical potential. The Kondo temperatures for different parameters are estimated by fitting the universal curves of spin susceptibility. We find that the Kondo temperature is almost a linear function of Rashba spin–orbit energy when the chemical potential is close to the edge of the conduction band. When the chemical potential is far away from the band edge, the Kondo temperature is independent of the spin–orbit coupling. These results demonstrate that, for single impurity problems in this system, the most important reason to change the Kondo temperature is the divergence of density of states near the band edge, and the divergence is induced by the Rashba spin–orbit coupling.